Reassignment of ’Triplophysa’ jiarongensis (Cypriniformes: Nemacheilidae) to Oreonectes Günther, 1868 - Liu, Xuan; Deng, Huaiqing; Liu, Zhijin; Zhou, Jiang (Zootaxa, 2019)
Specimens identified as Oreonectes jiarongensis (Cypriniformes: Nemacheilidae) were collected from a karst cave in Jiarong Town and Banzhai Township, Libo County, Guizhou, China. Several lines of morphological and molecular evidence suggested that this species was similar to species of Oreonectes Günther 1868 and not closely related to species of Triplophysa Rendal, 1933. The anterior and posterior nostrils of ’Triplophysa’ jiarongensis were separated by a short distance, and there was no secondary sexual dimorphism in male specimens. The Bayesian phylogenetic analysis based on cytochrome b recovered ’T.’ jiarongensis in a well-supported clade with Oreonectes daqikongensis, O. shuilongensis, O. furcocaudalis and O. platycephalus, sister to the Triplophysa clade. In addition, the genetic distances between ’T.’ jiarongensis and species of Oreonectes were low (O. daqikongensis: 0.114; O. shuilongensis: 0.106; O. platycephalus: 0.180), while distances to species of Triplophysa were higher (T. dorsalis: 0.233; T. yarkandensis: 0.282). Therefore, we reassign ’T.’ jiarongensis to Oreonectes. Based on this result, it is now clear that species of both Oreonectes and Triplophysa inhabit the same underground river system in Guizhou. However, as species of Oreonectes are only known from the southern part of Guizhou, it may be that O. jiarongensis inhabits the most northerly part of the range of this genus.